2019
DOI: 10.1136/bmjoq-2018-000577
|View full text |Cite
|
Sign up to set email alerts
|

Improving hepatitis C screening and diagnosis in patients born between 1945 and 1965 in a safety-net primary care clinic

Abstract: Individuals born between 1945–1965 represent 81% of all persons chronically infected with hepatitis C virus (HCV) in the USA and are largely unaware of their positive status. The baseline HCV screening rate in this population in an academic internal medicine clinic at a US hospital was less than 3.0%. The goal was to increase the rate of HCV screening in patients born between 1945 and 1965 to 20% within 24 months. The quality improvement team used the Plan Do Study Act Model. Outcome measures included HCV anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…This study consisted of two phases: intervention development (phase 1) and feasibility testing (phase 2). We developed a multilevel intervention prototype aimed at patients and providers to address barriers to HCV screening [ 7 ] based on our work, previous literature, theory-based interventions, and barriers and facilitators to HCV screening specifically [ 9 , 10 ]. This study was reviewed and approved by the authors’ Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…This study consisted of two phases: intervention development (phase 1) and feasibility testing (phase 2). We developed a multilevel intervention prototype aimed at patients and providers to address barriers to HCV screening [ 7 ] based on our work, previous literature, theory-based interventions, and barriers and facilitators to HCV screening specifically [ 9 , 10 ]. This study was reviewed and approved by the authors’ Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…Our aim statement was achievable and realistic based on 'SMART' goals 9 and based on previous QI projects from this clinic. [10][11][12][13][14][15][16]…”
Section: Problem Descriptionmentioning
confidence: 99%
“…We anticipated many challenges to optimise breast cancer screening rates in this unique patient population; therefore, we selected a 10% improvement within 1 year from the baseline rate. Our aim statement was achievable and realistic based on ‘SMART’ goals9 and based on previous QI projects from this clinic 10–16…”
Section: Introductionmentioning
confidence: 99%
“…Despite Centers for Disease Control and US Preventive Services Task Force recommendations for 1-time HCV screening in all baby boomers (adults born between 1945 and 1965) (12), uptake of HCV screening remains low in some settings. Studies have suggested that less than 20% of baby boomers received screening between 2013 and 2016 (13), and it is estimated that at least half of the 3 million persons infected with HCV in the United States remain undiagnosed, with many being unaware of their HCV status (14,15). Even among those who receive HCV screening, there is discontinuity in downstream processes among those with a positive result, including suboptimal HCV RNA testing and linkage to care.…”
Section: Introductionmentioning
confidence: 99%